(untitled) (Jurnal Agribisnis dan Agrowisata, 2025)
The Analysis of Primary Sector of Jembrana Regency. The economic development indicators can be studied using Gross Regional Domestic Product (GDP). The GDP of Kabupaten Jembrana consists of 17 sectors classified into three major groups, namely primary, secondary and tertiary sectors. The development of the primary sectors (the bases) is significantly influencing the growth of regional GDP; thus, the regional economic aspects planning process becomes well-organized after identifying the primary sectors (the bases) and the non-primary sectors (the non-bases) of the regency. The purpose of this study is to identify the primary sectors (the bases) and the non-primary sectors (the non-bases), as well as to understand the influence of the leading sector (the bases) of Kabupaten Jembrana economic situation. The data used in this study were the secondary data that derived from BPS of Kabupaten Jembrana and Bali Province in 2010-2019 and also supported by any related literature. The result showed that the leading sectors (the bases) in Kabupaten Jembrana are agriculture, forestry, fisheries, transportation, and warehousing sectors. In addition, the information, communication, and other competitive sectors in Kabupaten Jembrana consist of agriculture, forestry, fisheries, transportation, and warehousing. These findings also show the influence of Jembrana’s leading sector (the base) on the economic situation and have already been competitive. Finally, the most significant contributors to Jembrana’s GDP value are the agriculture, forestry, and fisheries sectors.